Ion Pillat descoperă Balcicul - Carmen Brăgaru (Revista de Istorie și Teorie Literară, 2011)
In Ion Pillat’s life and work the town of Balcic, a little sea-port on the Silver Coast of the Black Sea gained an amazing position in the 30s of the last century. A passionate reader and consumer of history and geography and a born traveler, the poet had the chance to visit from an early age an impressive number of regions and cities in Europe, from Normandy, Bretagne, Loire Valley, Bruges, Anvers, Venice, Delft, Hague, Amsterdam to Prague, Bratislava, Barcelona, Geneva, Vienna, Brussels, Berlin, Constantinople, Varna, Athens and many others. All these may have left their mark in a poem or at least in a verse in Ion Pillat’s poetry, but few were the places where he felt at home and which offered him the necessary refuge where he could be inspired and work passionately. The Florica estate, then the one of Miorcani and much later the vineyard of Izvorani were one by one the hospitable and inspiring places where Ion Pillat wrote constantly most of his famous poems. At a certain moment the town of Balcic compelled recognition in the gallery of blessed spaces for Ion Pillat’s poetry. Nevertheless the posterity knows only few details about the poet’s life and work there. Taking for granted an inexact piece of information asserted by Ion Pillat’s son, Dinu, according to which his father discovered the town of Balcic only in 1934, when he suddenly bought some land and built a house, all the biographers and researchers spread it with each new article, study or book, fixing it in the literary history. Our article – a first chapter taken from a larger study20 regarding Ion Pillat’s activity in Balcic – based on documents found in archives, manuscripts kept in libraries and the poet’s correspondence closely follows the movements before and after Ion Pillat’s discovery of the picturesque town.